Parent-Reported Burn-Specific Health-Related Quality of Life in Children 5–7 Years After Burns: A Multicenter Cross-Sectional Study - Marina C. Heijblom; J. Nicolaas Dijkshoorn; Marianne K. Nieuwenhuis; Anouk Pijpe; Cornelis H. van der Vlies; Margriet E. van Baar; Inge Spronk (European Burn Journal)
Surviving a burn can dramatically alter a child’s life, yet few studies examined long-term health-related quality of life (HRQL). This study assessed HRQL 5–7 years post-burn in children with mild/intermediate and severe burns and identified associated factors. Parents of children (5− < 18 years) who were hospitalized or had burn surgery between 08/2011 and 09/2012 completed the Burn Outcomes Questionnaire (BOQ). Outcomes were compared between two subgroups: children with mild/intermediate burns (<10% total body surface area (TBSA) burned) versus severe burns ((1) aged <10 years old at the time of injury with >10% (TBSA) burned; (2) aged ≥10 years with >20% TBSA burned; or (3) >5% full-thickness burns). A total of 102 children were included (mean age at survey: 8.4 (3.0) years; mean former TBSA: 7.1%). At a mean of 5.7 years post-burn, many parents rated their child’s health as excellent (46.1%) or very good (35.3%), with few reporting issues with ‘pain’ (2.3%), ‘physical function and sports’ (1.6%), and ‘upper extremity function’ (0.9%). Parents of children with severe burns indicated significantly more problems with ‘appearance’ (89.2% versus 71.5%; p = 0.014) and ‘parental concern’ (94.1% versus 84.8%; p = 0.021). Upper limb burns, facial burns, burn size, length of hospital stay, full-thickness burns, and the number of surgeries predicted poorer outcomes. In general, these findings indicate positive long-term HRQL, though especially children with full-thickness burns and/or surgical interventions face a higher risk of reduced HRQL. The results can be used to inform children and their families about the long-term implications. Furthermore, healthcare professionals can use these insights to identify children at higher risk of poorer long-term HRQL.